Practice-oriented legal education at Kazan University: D.I. Meyer's view and modern approach - S.B. Seletskaya; R.I. Sitdikova; A.N. Shpagonov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The similarities between the views on legal education introduced by D.I. Meyer and reflected in the modern federal state educational standards – practice-oriented learning – have been considered. D.I. Meyer’s ideas have been discussed based on his work “On the Importance of Practice in the System of Modern Legal Education” (1855). The value of D.I. Meyer’s studies is that he was the first in Russia to investigate the methodology of teaching legal disciplines and to emphasize the need to combine theory and practice. It has been concluded that practice-oriented legal education at Kazan University has evolved and still dominates as the main approach to teaching legal disciplines. In addition, special attention has been paid to D.I. Meyer’s advice given to ordinary people in the presence of students, i.e., he worked at the legal clinic, which was organized by him at Kazan University during the 1840s. The continuity of D.I. Mayer’s traditions has been shown. They have shaped into the main principles of the legal clinic at Kazan Federal University, the directions of its activity and the education of students.